PRELIMINARY STUDY OF SPECIES COMPOSITION AND DISTRIBUTION OF ECONOMICALLY VALUABLE PRAWNS IN THE NORTHEASTERN COASTAL WATERS OF VIETNAM - Thinh, Do Dinh (Marine Research in Indonesia, 2012)
The northeastern coastal waters of Vietnam contains diverse and abundant prawns with economic importance. In recent years, overexploitation and marine environmental pollution have led to the decrease of prawns. The purpose of this study is to identify the current diversity and distribution of prawns in this region. Prawns were sampled by a trawl net at four sites in 2011. A total of 21 species of three families of the superfamily Penaeoidea was distributed in this area. The family Penaeidae is the most diverse with 19 species, while each of family Sicyoniidae and Solenoceridae has only one species.